(3OQGSGJ aj fTCI h JWhQ GdZQa GdJLGQjI GdYQHjI (B/s - (3GdYHjOj, UdGM YQjHj YHGSs ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2011)
(3GdLPhQ GdJGQjNjI dfTCI GdZQa GdJLGQjI(B- (3fTCI hJWhQ GdZQa GdJLGQjI GdYQHjI(B- (3GdEJMGO GdYGe dZQa GdJLGQjI hGdUfGYI hGdRQGYI ddHdGO GdYQHjI(B- (3GdZQa GdJLGQjI GdYQHjI GdCLfHjI GdeTJQcI(B- (3ZQaI JLGQI cQhc(B- (3ZQaI JLGQI hUfGYI GdHMQjfs
(3GdeQGLY U(B.227s
Keywords: (3GdJLGQIs; (3GdJLGQI GdYQHjI GdeTJQcIs